Reception History, Early Pentecostal Literature, and the Pneumatology of the Apocalypse - Johnson, David R. (Journal of pentecostal theology, 2018)
This article examines the early Pentecostal literature in the Wesleyan-Holiness and Finished-Work streams of the tradition by utilizing Wirkungsgeschichte to consider the ways in which early Pentecostals explored the pneumatology of the Apocalypse from 1906–1918. This article reveals that the early Pentecostal interpretations were attentive to the pneumatology of the Apocalypse and that their pneumatic experiences were influenced by language and imagery from the Apocalypse.